DETERMINASI MARKET SHARE DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY (Survey pada PT Indofood Sukses Makmur Tbk tahun 2009-2018) - DARA SITI NURJANAH; Andri Helmi Munawar; Dian Hadiani; Tita Wulandari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
ABSTRACT This research was conducted with the aim to empirically examine the influence of MarketShare and Debt To Equity Ratio (DER) on Return On Equity (ROE) at PT Indofood Sukses Makmur Tbk Year 2009-2018 partially or silmutanously. The research approach used in this study is a quantitative method. The sampling technique used is non probability sampling using a purposive sampling research method. The population of this study is the company's financial statement data, namely PT Indofood Sukses Makmur Tbk in 2009-2018. In this study using secondary data types obtained at the Indonesia Stock Exchange. The secondary data is then processed and analyzed using time series analysis. Multiple regression analysis, hypothesis testing using the f test and t test. Based on the results of the study the influence of MarketShare and Debt To Equity Ratio on Return On Equity of 75.2%. Hypothesis test results explain that MarketShare and Debt To Equity Ratio (DER) together have a significant effect on Return On Equity (ROE) at PT Indofood Sukses Makmur Tbk. The partial effect of MarketShare on Return on Equity (ROE) is 60.09 %, and hypothesis testing shows MarketShare has a positive and significant effect. Large influence partially Debt To Equity Ratio (DER) on Return On Equity (ROE) is 15.10%, and hypothesis testing shows no significant effect on Debt To Equity Ratio (DER) of Return On Equity (ROE) at PT Indofood Sukses Makmur Tbk in 2009-2018